Experimental endocrine therapies promote epithelial cytodifferentiation and ciliogenesis in the gerbil female prostate - Alcantara Santos, Fernanda Cristina; Falleiros-Junior, Luiz Roberto; Corradi, Lara Silvia; Leite Vilamaior, Patricia Simone; Taboga, Sebastiao Roberto (Springer, 2007)
The incidence of ciliated cells in the prostate gland of the female gerbil (Meriones unguiculatus) is uncommon and apparently becomes more frequent during androgen (testosterone cypionate) and anti-estrogen (letrozole) endocrine therapies. To evaluate the effects of such drug therapies on the induction of ciliogenesis in the glandular epithelium of female prostate glands, adult female gerbils aged 90 days were treated for 14 days with testosterone and letrozole after which their prostate glands were removed for histological, ultrastructural, and serological analyses. The cytodifferentiation of the ciliated phenotype in the alveolar epithelium became more frequent after both the testosterone and the letrozole treatments. The ciliogenesis phenomenon of the epithelial cells in the prostate gland of female gerbils thus appears to be induced by variations in the increase of androgen levels.
Keywords: female prostate; ciliogenesis; testosterone; letrozole; epithelium; Mongolian gerbil, Meriones unguiculatus (Rodentia)